2014
DOI: 10.1021/ic500032f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Phosphine Steric and Electronic Profile on the Rh-Promoted Dehydrocoupling of Phosphine–Boranes

Abstract: The electronic and steric effects in the stoichiometric dehydrocoupling of secondary and primary phosphine–boranes H3B·PR2H [R = 3,5-(CF3)2C6H3; p-(CF3)C6H4; p-(OMe)C6H4; adamantyl, Ad] and H3B·PCyH2 to form the metal-bound linear diboraphosphines H3B·PR2BH2·PR2H and H3B·PRHBH2·PRH2, respectively, are reported. Reaction of [Rh(L)(η6-FC6H5)][BArF4] [L = Ph2P(CH2)3PPh2, ArF = 3,5-(CF3)2C6H3] with 2 equiv of H3B·PR2H affords [Rh(L)(H)(σ,η-PR2BH3)(η1-H3B·PR2H)][BArF4]. These complexes undergo dehydrocoupling to gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
5
25
0
Order By: Relevance
“…The determined molecular structure in the solid state confirms the structural assignment (Figure ). The Fe−H1 B1 , B−H1 B1 and B−P bond lengths are in the same range as those in related complexes …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The determined molecular structure in the solid state confirms the structural assignment (Figure ). The Fe−H1 B1 , B−H1 B1 and B−P bond lengths are in the same range as those in related complexes …”
Section: Resultssupporting
confidence: 57%
“…The FeÀH1 B1 ,B ÀH1 B1 andB ÀPb ond lengths are in the same range as those in related complexes. [3,7,13,14,16,[29][30][31][32][33][34][35][36] Isocyanides such as tBuNC are neutrala nd more bulky than the other ligands, but they are also good s-donorl igands. The reaction of I with tBuNC resulted in the formation of a1:1 mixture of two different products according to the 31 P{ 1 H} NMR spectrum of the reaction mixture (Scheme 2).…”
Section: Ancillary-ligand-induced Reactivitymentioning
confidence: 99%
“…This provides evidence for the mechanism proposed in Scheme 69 in which the Rh I σ-bound linear diboraphosphine complex is in equilibrium with the P-H-activated Rh III octahedral complex as such a process would allow interconversion of the Rh III diastereomers. Such a diastereomeric bias may afford some control of polymer tacticity in dehydropolymerisation reactions [175]. Interestingly, the use of a chiral chelating phosphine ligand on rhodium resulted in a further bias towards one diastereoisomer, but the absolute configuration was not determined.…”
Section: Mechanistic Investigation Into the Rhodium-catalysedmentioning
confidence: 99%
“…When electron-withdrawing substituents are present on phosphorus, the P-H bond more readily undergoes P-H oxidative addition, making Rh III species favoured [174]. In a follow-up report, secondary phosphine-boranes bearing fluorinated substituents H 3 B · P( p-F 3 C-C 6 H 4 ) 2 H and H 3 B · P(m-(F 3 C) 2 C 6 H 3 ) 2 H were found to dehydrocouple at a faster rate than H 3 B · PPh 2 H using the same [Rh(dppp)] + system [175]. However, stoichiometric reactions showed that the weakening of the P-B bond by the presence of the electron-withdrawing groups caused P-B bond cleavage and hence catalyst deactivation by the formation of [Rh(dppp)(PR 2 [176].…”
mentioning
confidence: 90%
“…TBE in 1,2-F 2 C 6 H 4 solvent, by addition of the alkene to in situ generated 6, Scheme 9. After 45 minutes a new peak is apparent in the 1 40,42,43 After a further 12 hours all of 6 was consumed, but a greater proportion of 8 (ca. 33%) was also present.…”
Section: View Article Onlinementioning
confidence: 99%